A Late-Stage Strategy for the Functionalization of Triazolium-Based NHC Catalysts - Ozboya, Kerem E.; Rovis, Tomislav (Synlett, 2014)
A strategy for the diversification of triazolium-based catalysts is presented. This method is based on the reduction to the triazoline, which serves as a suitable and stable substrate for palladium-mediated cross-coupling, followed by trityl cation mediated reoxidation to the triazolium.
Keywords: NHC Catalysis; organocatalysis; asymmetric catalysis